Smart Mediterranean Logics. Old - New Dimensions and Transformations of Territories and Cites-Ports in Mediterranean - Emanuela Nan (TeMA: Journal of Land Use, Mobility and Environment, 2014)
The land coast, with particular emphasis the port-city, are in fact used more and more like a menu in which different users increasingly move freely according to their needs. The new definition parameters with respect to which the landscapes are recognizable, articulating configurations, immutable, and not concluded, but on the contrary, variables are always open and more leads, not the placement of functions, but the interaction between subjects, and actually pushed social, cultural, political and economic. The port city now seems more like a miscellany, and a composite variable, the definition of which combine multiple devices and whose understanding and operational management appears to be no longer in the perimeter of registers and formal, but the identification of rules and tactics logical drive and able to predict particular outcomes and the evolution of the different dynamics and vocations. 'Dream City', 'Dream Lands' and 'Dream Country' will constitute the new benchmarks in the definition of geographies based on imagination, perception and use of spaces and scenarios from the sensitivity of each individual and class user, until the size of the global imaginary fantasy, with respect to which space, urbanity and territories are distinguished as 'complementary' or 'complementary' depending on the specific 'action brands' and 'areas of opportunity'.